Anti-ultraviolet anti-aging light-resistant material as well as preparation method and application thereof
By adding modified fillers and auxiliary additives to high-density polyethylene materials, polymer light-proof materials with excellent ultraviolet resistance and anti-aging properties are prepared, which solves the problem of yellowing and deterioration of polymer materials due to ultraviolet irradiation. Significantly extends service life and improves mechanical properties.
Patent Information
- Application Number
- CN202510059547.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the semiconductor manufacturing industry, polymer materials are prone to yellowing, deterioration and mechanical properties due to ultraviolet irradiation, resulting in a shortened service life, and the prior art is difficult to effectively solve this problem.
Using high-density polyethylene as the base material, a polymer light-proof material with excellent ultraviolet resistance and anti-aging properties was prepared by adding modified fillers and other auxiliary additives. The modified filler consists of modified titanium dioxide and modified zirconium silicate, and is prepared by sonication and ball mill treatment. Combined with components such as styrene triazole and polyethylene glycol, the material's ultraviolet resistance is optimized.
This material significantly improves the barrier and absorption capacity of ultraviolet rays, extends the service life of polymer materials, avoids yellowing and deterioration, and enhances the stability of mechanical properties.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials, and relates to an anti-ultraviolet, anti-aging and light-shielding material and a preparation method and application thereof. Background Art
[0002] In the semiconductor manufacturing industry, in addition to the need to solve the problem of significant adverse effects on the semiconductor itself, the quality of liquid crystals, and the yield rate, in order to solve the problem of shortened storage period due to deterioration of drugs, containers with ultraviolet shielding and excellent anti-aging properties are required. It can prevent the yellowing, degradation and mechanical performance decline of polymer materials caused by ultraviolet radiation, and extend the service life of polymer materials in outdoor applications.
[0003] Therefore, it is necessary to develop a UV-proof, anti-aging and light-proof material that can be used to prepare a light-proof container. Summary of the invention
[0004] The purpose of the present invention is to provide an anti-ultraviolet and anti-aging light-shielding material and a preparation method thereof. The present invention uses high-density polyethylene as a base material and prepares a polymer light-shielding material with excellent ultraviolet protection and anti-aging properties by adding modified fillers and other auxiliary additives.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An anti-ultraviolet and anti-aging light-shielding material comprises the following raw materials in parts by weight: 35-45 parts of high-density polyethylene, 3-5 parts of modified fillers, 1-3 parts of light stabilizers, 1-3 parts of antioxidants, 1-2 parts of lubricants, 1-4 parts of calcium carbonate, and 1-3 parts of plasticizers; The preparation process of the modified filler is as follows: Benzotriazole, polyethylene glycol and anhydrous ethanol in a mass ratio of (3-5): (5-10): (50-60) were mixed, and ultrasonic treatment was performed for 35 minutes to obtain a mixed solution A, and titanium dioxide was added and mixed for 18-24 hours, and dried at 85°C for 10 hours to obtain modified titanium dioxide; Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution B with a mass concentration of 2-3 mg / L, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution B to 8.5, and zirconium silicate was added, and the mixture was stirred at room temperature for 24 hours, and then filtered and dried to obtain modified zirconium silicate; The modified titanium dioxide and the modified zirconium silicate were mixed in a mass ratio of 1:1, ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the modified filler.
[0006] As a preferred technical solution of the present invention, the mass ratio of the mixed solution A to titanium dioxide is 10:(1-2).
[0007] As a preferred technical solution of the present invention, the mass ratio of the mixed solution B to zirconium silicate is 10:(1-3).
[0008] As a preferred technical solution of the present invention, the plasticizer is one of pentaerythritol tetraester, dioctyl terephthalate, trioctyl trimellitate and dioctyl sebacate.
[0009] As a preferred technical solution of the present invention, the lubricant is one of polyethylene wax, butyl stearate, ethylene bisstearamide and silicone powder.
[0010] As a preferred technical solution of the present invention, the light stabilizer is UV1130.
[0011] As a preferred technical solution of the present invention, the antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 245.
[0012] A method for preparing an anti-ultraviolet and anti-aging light-shielding material comprises the following steps: S1. Heat high-density polyethylene to 150-200°C by weight, then add the modified filler and stir for 0.5-1h to obtain mixture 1; S2, mix the light stabilizer, antioxidant, lubricant, antistatic agent, calcium carbonate and plasticizer evenly, heat to 100-120°C and stir for 20-30 min, then cool naturally to room temperature and continue stirring for 10-15 min, wherein the stirring speed is 1000-1500 r / min, to obtain mixture 2; S3, mixing mixture 1 and mixture 2 and pressurizing them to 1-5 MPa, and maintaining the pressure for 10-15 minutes to obtain the anti-ultraviolet and anti-aging light-shielding material.
[0013] As a preferred technical solution of the present invention, in step S1, the stirring speed is 400-800 r / min.
[0014] An application of an anti-ultraviolet and anti-aging light-proof material. The anti-ultraviolet and anti-aging light-proof material can be used to prepare a light-proof container. The light-proof container includes a light-proof bottle and a light-proof barrel.
[0015] Titanium dioxide has a blocking and absorbing effect on ultraviolet rays, so it has a strong anti-ultraviolet ability. In the present invention, polyethylene glycol and benzotriazole are used to modify titanium dioxide, wherein polyethylene glycol, as a high molecular organic matter, has excellent dispersibility and wettability. When it is compounded with titanium dioxide, the surface properties of titanium dioxide particles can be effectively improved, so that it can be more evenly dispersed in the matrix material. This uniform dispersion is not only conducive to the effective absorption and scattering of ultraviolet rays by titanium dioxide particles, but also reduces the agglomeration phenomenon between particles, thereby improving the overall anti-ultraviolet performance. Benzotriazole is an excellent ultraviolet absorber that can absorb ultraviolet rays with a wavelength of 290 to 390 nanometers. When benzotriazole is mixed with titanium dioxide, the two can produce a synergistic effect and jointly improve the anti-ultraviolet performance of the material. In addition, polyethylene glycol and benzotriazole form stable hydrogen bonds through mutual adsorption with the surface of titanium dioxide. This interaction can change the electronic structure of the titanium dioxide surface, further optimizing its absorption and scattering ability to ultraviolet rays.
[0016] When modified titanium dioxide is added to materials, it can effectively absorb and transform this harmful UV energy, thereby greatly slowing down the aging process of the material.
[0017] The high refractive index of zirconium silicate enables it to effectively scatter and reflect light in the visible and ultraviolet range. This scattering effect can reduce the direct exposure of ultraviolet rays to the material, thereby playing an anti-ultraviolet role. Dopamine is self-polymerized under alkaline conditions to form polydopamine. The functional groups in the polydopamine molecule, such as catechol and amine, can absorb or scatter ultraviolet rays, thereby reducing the direct exposure of ultraviolet rays to zirconium silicate. This absorption or scattering effect helps to reduce the photodegradation or photoaging of the zirconium silicate surface caused by ultraviolet radiation, thereby improving the anti-ultraviolet and anti-aging properties of zirconium silicate.
[0018] And the adhesion of polydopamine enables it to effectively adhere to the surface of zirconium silicate, thereby improving the surface properties of zirconium silicate, such as increasing hydrophilicity, reducing surface defects, etc., thereby indirectly improving its aging resistance, and helping the modified zirconium silicate and modified titanium dioxide to mix evenly. The prepared modified filler has excellent UV resistance and aging resistance.
[0019] Beneficial effects of the present invention: The present invention uses high-density polyethylene as a base material, and prepares a polymer light-shielding material with excellent UV protection and aging resistance by adding modified fillers and other auxiliary additives. The modified filler is a mixture obtained by ball milling modified zirconium silicate and modified titanium dioxide. The UV resistance of the modified filler itself is utilized, wherein polyethylene glycol and benzotriazole optimize the UV resistance and aging resistance of titanium dioxide, and polydopamine can also help improve the photodegradation or photoaging phenomenon of the modified zirconium phosphate by absorbing or scattering ultraviolet rays. DETAILED DESCRIPTION
[0020] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0021] In the following examples and comparative examples: Benzotriazole: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: H801875; Polyethylene glycol: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: P103737; Titanium dioxide: purchased from Shanghai Yaotian New Materials Technology Co., Ltd., 30 nm; Dopamine: purchased from Shanghai Dexin Zhiyuan Biotechnology Co., Ltd. Zirconium silicate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: Z820667; High-density polyethylene: Model is Qatar TR571; UV1130: purchased from Tianjin Lianlong New Materials Co., Ltd.; Antioxidant 1010: purchased from Guangzhou Dayin New Materials Co., Ltd. Polyethylene wax: purchased from Shenyang Elex Chemical Co., Ltd. Calcium carbonate: purchased from Shanghai Nuocheng Pharmaceutical Co., Ltd.; Dioctyl terephthalate: purchased from Wuhan Jiyesheng Chemical Co., Ltd.
[0022] Example 1 Preparation of modified filler: Phenyltriazole, polyethylene glycol and anhydrous ethanol in a mass ratio of 3:5:50 were mixed, and ultrasonic treatment was performed for 35 minutes to obtain a mixed solution A, and titanium dioxide was added and mixed for 18 hours, and dried at 85°C for 10 hours to obtain modified titanium dioxide, wherein the mass ratio of the mixed solution A to titanium dioxide was 10:1; Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution B with a mass concentration of 2 mg / L, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution B to 8.5, and zirconium silicate was added, and the mixture was stirred at room temperature for 24 hours, filtered, and dried to obtain modified zirconium silicate, wherein the mass ratio of the mixed solution B to the zirconium silicate was 10:1; The modified titanium dioxide and the modified zirconium silicate were mixed in a mass ratio of 1:1, ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the modified filler.
[0023] Preparation of UV-proof, anti-aging and light-proof materials: S1. Heat 35 parts of high-density polyethylene to 150° C. by weight, then add 3 parts of modified filler and stir for 0.5 h at a stirring speed of 400 r / min to obtain mixture 1; S2, 1 part of UV1130, 1 part of antioxidant 1010, 1 part of polyethylene wax, 1 part of calcium carbonate, and 1 part of dioctyl terephthalate were mixed evenly, heated to 100°C and stirred for 20 min, then naturally cooled to room temperature and continued to stir for 10 min, wherein the stirring speed was 1000 r / min, to obtain mixture 2; S3, mixing mixture 1 and mixture 2 and pressurizing them to 1 MPa, and maintaining the pressure for 10 minutes to obtain the anti-ultraviolet and anti-aging light-shielding material.
[0024] Example 2 Preparation of modified filler: Benzotriazole, polyethylene glycol and anhydrous ethanol in a mass ratio of 4:7:55 were mixed, and ultrasonic treatment was performed for 35 minutes to obtain a mixed solution A, and titanium dioxide was added and mixed for 20 hours, and dried at 85°C for 10 hours to obtain modified titanium dioxide, wherein the mass ratio of the mixed solution A to titanium dioxide was 10:1.5; Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution B with a mass concentration of 2.5 mg / L, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution B to 8.5, and zirconium silicate was added, and the mixture was stirred at room temperature for 24 hours, filtered, and dried to obtain modified zirconium silicate, wherein the mass ratio of the mixed solution B to the zirconium silicate was 10:2; The modified titanium dioxide and the modified zirconium silicate were mixed in a mass ratio of 1:1, ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the modified filler.
[0025] Preparation of UV-proof, anti-aging and light-proof materials: S1. Heat 40 parts of high-density polyethylene to 170° C. by weight, then add 4 parts of modified filler and stir for 0.8 h at a stirring speed of 600 r / min to obtain mixture 1; S2, 2 parts of UV1130, 2 parts of antioxidant 1010, 1.5 parts of polyethylene wax, 3 parts of calcium carbonate, and 2 parts of dioctyl terephthalate were mixed evenly, heated to 110°C and stirred for 25 min, then naturally cooled to room temperature and continued stirring for 13 min, wherein the stirring speed was 1300 r / min, to obtain mixture 2; S3, mixing mixture 1 and mixture 2 and pressurizing them to 3 MPa, and maintaining the pressure for 13 minutes to obtain the anti-ultraviolet and anti-aging light-shielding material.
[0026] Example 3 Preparation of modified filler: Phenyltriazole, polyethylene glycol and anhydrous ethanol in a mass ratio of 5:10:60 were mixed, and ultrasonic treatment was performed for 35 minutes to obtain a mixed solution A, and titanium dioxide was added and mixed for 24 hours, and dried at 85°C for 10 hours to obtain modified titanium dioxide, wherein the mass ratio of the mixed solution A to titanium dioxide was 10:2; Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution B with a mass concentration of 3 mg / L, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution B to 8.5, and zirconium silicate was added, and the mixture was stirred at room temperature for 24 hours, filtered, and dried to obtain modified zirconium silicate, wherein the mass ratio of the mixed solution B to the zirconium silicate was 10:3; The modified titanium dioxide and the modified zirconium silicate were mixed in a mass ratio of 1:1, ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the modified filler.
[0027] Preparation of UV-proof, anti-aging and light-proof materials: S1. Heat 45 parts of high-density polyethylene to 200°C by weight, then add 5 parts of modified filler and stir for 1 hour at a stirring speed of 800 r / min to obtain mixture 1; S2, 3 parts of UV1130, 3 parts of antioxidant 1010, 2 parts of polyethylene wax, 4 parts of calcium carbonate, and 3 parts of dioctyl terephthalate were mixed evenly, heated to 120°C and stirred for 30 min, then naturally cooled to room temperature and continued stirring for 15 min, wherein the stirring speed was 1500 r / min, to obtain mixture 2; S3, mixing mixture 1 and mixture 2 and pressurizing them to 5 MPa, and maintaining the pressure for 15 minutes to obtain the anti-ultraviolet and anti-aging light-shielding material.
[0028] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the titanium dioxide in Comparative Example 1 is not modified, and the other operations are the same.
[0029] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the zirconium silicate in Comparative Example 2 is not modified, and the other operations are the same.
[0030] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that the preparation process of the modified filler in Comparative Example 3 is: titanium dioxide and zirconium silicate in a mass ratio of 1:1 are mixed, ball milled at a speed of 400 r / min for 3 hours, and passed through a 200-mesh sieve to obtain the modified filler; wherein titanium dioxide and zirconium silicate are not modified, and the other operations are the same.
[0031] Performance Test: Test method: In an environment with a temperature of 60°C and a relative humidity of 55%, the UVA-340 ultraviolet lamp is 15 cm away from the sample and the light intensity is 0.5 W / m 2 , after UV irradiation for 168 hours, let it stand for 2 hours, and measure the tensile strength of the materials of Examples 1-3 and Comparative Examples 1-3 before and after UV irradiation; Xenon lamp aging test: According to GB / T16422.2 standard, the elongation at break of the material after aging test is measured; Tensile strength and elongation at break: measured in accordance with GB / T1040.2-2006 standard; Each group was measured 5 times and the average value was taken. The results are shown in Table 1: Table 1 Performance test data of Examples 1-3 and Comparative Examples 1-3
[0032] According to the above data, the tensile strength and elongation at break of the comparative example are smaller than those of the embodiment, and the material prepared in the embodiment has good aging resistance and UV resistance.
[0033] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. An anti-ultraviolet and anti-aging light-shielding material, characterized in that: The invention comprises the following raw materials in parts by weight: 35-45 parts of high-density polyethylene, 3-5 parts of modified filler, 1-3 parts of light stabilizer, 1-3 parts of antioxidant, 1-2 parts of lubricant, 1-4 parts of calcium carbonate and 1-3 parts of plasticizer; The preparation process of the modified filler is as follows: Benzotriazole, polyethylene glycol and anhydrous ethanol in a mass ratio of (3-5): (5-10): (50-60) were mixed, and ultrasonic treatment was performed for 35 minutes to obtain a mixed solution A, and titanium dioxide was added and mixed for 18-24 hours, and dried at 85°C for 10 hours to obtain modified titanium dioxide; Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution B with a mass concentration of 2-3 mg / L, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution B to 8.5, and zirconium silicate was added, and the mixture was stirred at room temperature for 24 hours, and then dried to obtain modified zirconium silicate; The modified titanium dioxide and the modified zirconium silicate were mixed in a mass ratio of 1:1, ball-milled at a speed of 400 r / min for 3 h, and passed through a 200-mesh sieve to obtain the modified filler.
2. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The mass ratio of the mixed solution A to titanium dioxide is 10:(1-2).
3. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The mass ratio of the mixed solution B to zirconium silicate is 10:(1-3).
4. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The plasticizer is one of pentaerythritol tetraester, dioctyl terephthalate, trioctyl trimellitate and dioctyl sebacate.
5. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The lubricant is one of polyethylene wax, butyl stearate, ethylene bis stearamide and silicone powder.
6. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The light stabilizer is UV1130.
7. The anti-ultraviolet and anti-aging light-shielding material according to claim 1, characterized in that: The antioxidant is one or more of antioxidant 1010, antioxidant 168, antioxidant 264, and antioxidant 245.
8. A method for preparing the anti-ultraviolet and anti-aging light-shielding material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. Heat high-density polyethylene to 150-200°C by weight, then add the modified filler and stir for 0.5-1h to obtain mixture 1; S2, mix the light stabilizer, antioxidant, lubricant, antistatic agent, calcium carbonate and plasticizer evenly, heat to 100-120°C and stir for 20-30 min, then cool naturally to room temperature and continue stirring for 10-15 min, wherein the stirring speed is 1000-1500 r / min, to obtain mixture 2; S3, mixing mixture 1 and mixture 2 and pressurizing them to 1-5 MPa, and maintaining the pressure for 10-15 minutes to obtain the anti-ultraviolet and anti-aging light-shielding material.
9. The method for preparing the anti-ultraviolet and anti-aging light-shielding material according to claim 8, characterized in that: In step S1, the stirring speed is 400-800 r / min.
10. An application of the anti-ultraviolet and anti-aging light-shielding material according to any one of claims 1 to 9, characterized in that: The anti-ultraviolet and anti-aging light-proof material can be used to prepare light-proof containers, and the light-proof containers include light-proof bottles and light-proof barrels.
Citation Information
Patent Citations
High-shading anti-weathering high-density polyethylene material
CN106117696A
Thermoplastic high voltage cable insulating material and preparation method thereof
CN106543563A
Polyethylene / montmorillonoid-supported titanium dioxide composite material and preparation method thereof
CN106633299A
Light protective bottle design
CN107743507A
Polydopamine pesticide microcapsule and preparation method thereof
CN109287646A